Achieving ACGME Clinical Informatics Fellowship Accreditation: A Chronicle of Our Institution's Journey - Chamala, Srikar; Keefer, Matthew S.; McGuire, Troy; Diaz, Leticia; Luberti, Anthony A.; Lehmann, Christoph U.; Schmidt, Ryan J. (Applied Clinical Informatics, 2025)
Clinical informatics (CI) is a dynamic field at the intersection of health care, technology, and information science, aimed at enhancing health care delivery and patient outcomes. CI fellowship programs prepare physicians to lead and apply health information technologies that drive improvements in clinical care, system efficiency, and innovation. Achieving Accreditation Council for Graduate Medical Education (ACGME) accreditation for such programs is crucial for standardizing training and ensuring the development of a competent workforce.This study aims to share our institution's experience at Children's Hospital Los Angeles in obtaining ACGME accreditation for a CI fellowship program, highlighting key steps and strategies.A multidisciplinary steering committee, including institutional leaders and CI experts, was formed. Key activities included a needs assessment, curriculum development, securing institutional support, and engaging with external advisors from accredited CI programs. The curriculum was designed to align with ACGME core competencies and the American Board of Preventive Medicine's CI subspecialty requirements. Extensive documentation, including rotation schedules and evaluation forms, was prepared for submission.Our CI fellowship program received ACGME accreditation. Essential components that contributed to our success included strong institutional support, a well-defined curriculum integrating clinical and non-clinical rotations, and strategic faculty involvement across various informatics domains. Guidance from experienced directors at established CI programs was instrumental in expediting our application process and ensuring program readiness. The development of detailed documentation, such as a block diagram and competency-based evaluations, was crucial in demonstrating compliance with ACGME requirements.Our experience of achieving ACGME accreditation underscores the importance of assembling a diverse steering committee, engaging external expertise, and securing robust faculty participation. The strategies and insights gained from our accreditation journey can serve as a roadmap for other institutions aiming to establish CI fellowship programs, which are vital for training future leaders in CI and advancing health care innovation.
Keywords: clinical informatics; fellowship; ACGME accreditation; graduate medical education; physician; workforce; ACGME; medical informatics; CHLA